EVALUASI KUALITAS PERAIRAN DALAM PEMBENIHAN IKAN KERAPU TIKUS (Cromileptis altivelis) Di HATCHERY PERAIRAN TANJUNG RIAU BATAM - Aliah, Ratu Siti (BPPT)
An evaluation of the water quality at the hatchery of Tanjung Riau was conducted to understand the water quality status at the several place of the hatchery unit such as brood stock tanks, larva rearing tank, water storage tank, fi ngerling tank as well as the source of the water supply. The water quality status of Tanjung Riau generally is in a good condition to support the hatchery activities, but for turbidity and salinity were in the exceed and below the normal status and its infl uence on the spawning activity. To overcome the problem on the spawning of the brood stock, the improving of water supply with higher salinity and low turbidity should be set up to ensure the succeeded of the spawning.Key words : Water quality, grouper brood stock, hatchery,Tanjung Riau Batam